PESTICIDES AND AQUATIC ECOSYSTEMS - Konar, S K (Indian Journal of Fisheries, 2011)
A survey made in West Bengal to evaluate the influence of pesticides onaqustic ecosystems showed that pesticides killed many fisheÂ» in Punarbbava River,West Danajpur, in August 1970. The paddy fields near the river received the insecticides:DDVP, phosphamidon and parathion. The tissues of gills, alimentarytract, liver and brain of the exposed carp {Labeo rohita) and catfish {Heteropneustesfossilis) were found severely damaged. The pesticide residue in fish wasin such level that may cause hazard to fish eaters